Community engagement in Australian local governments: a closer look and strategic implications. Issue 4 (4th July 2019) - Christensen, Helen E.; McQuestin, Dana
ABSTRACT: Public input into decision-making through participatory and deliberative democratic practices has become a widely accepted and legislated responsibility of Australian local governments. At any one time, councils are leading submission processes, workshops and online surveys on a multitude of projects, ranging from long-term community strategic plans to public art projects. The increase in these practices has been exponential, leaving little time for critical reflection. The lack of empirical data to illustrate how community engagement is understood and practised in different councils has hindered sector-wide reflection. This paper presents the findings of the 'Local Government Community Engagement Census', a survey of 175 councils – approximately half – from 4 of Australia's eastern states. This sectoral snapshot provides a picture of how councils understand, prioritise and practise community engagement, allowing critical reflection, an interpretation of implications and suggesting areas for future research.